The impact of cancer information overload on negative emotions in newly diagnosed lung cancer patients: the mediating role of fear of progression and the moderating role of social support - Xu, Fan; Zhang, Jiquan; Li, Qiao; Wang, Jing; Zhang, Ping; Dai, Weimin; Xie, Shaoju; Zhong, Xiaoli (Frontiers in Psychiatry, 2025)
BackgroundThe high incidence of negative emotions among lung cancer patients has become a significant challenge to global public health. Newly diagnosed patients may experience cancer information overload (CIO) when exposed to a large amount of uncertain cancer-related information within a short time. However, research on the relationship between CIO and negative emotions, and the roles of Fear of Progression (FoP) and social support, is still lacking.ObjectiveTo explore the mediating effect of FoP between CIO and negative emotion in newly diagnosed lung cancer patients, and the moderating role of social support among CIO, FoP and negative emotion.MethodThis study adopted a cross-sectional survey design. From October 2024 to February 2025, newly diagnosed lung cancer patients were recruited as research subjects from the oncology departments of three tertiary hospitals in Deyang City, China. Through the General Information Questionnaire, Cancer Information Overload Scale (CIOS), Fear of Progression Questionnaire-Short Form (FoP-Q-SF), Hospital Anxiety and Depression Scale (HADS) and the Social Support Rating Scale (SSRS) were used to investigate patients’ CIO, FoP, negative emotions and social support, and a total of 358 valid questionnaires were retrieved. All data were processed using SPSS 26.0, and the mediating effect and moderating effect were tested using the Process plugin.ResultsThe incidence of anxiety was 56.1% (201/358), and the incidence of depression was 53.1% (190/358). CIO had a positive predictive effect on FoP (β=0.338, P < 0.001) and negative emotion (β=0.375, P < 0.001). FoP has a positive predictive effect on negative emotion (β=0.342, P < 0.001), and FoP plays a mediating role between CIO and negative emotion (β= 0.115, 95%CI=[0.072, 0.166]). Social support plays a negative moderating role between FoP and negative emotion, with a moderating index of -0.124 and 95%CI=[-0.214,-0.033].ConclusionPatients with newly diagnosed lung cancer bear a heavy burden of anxiety and depression, which urgently needs attention. CIO plays a mediating role between FoP and negative emotion. Social support weakens the positive predictive effect of FoP on negative emotion. Our research results provide new insights and methods for supporting the improvement of negative emotions in lung cancer patients.